2012
DOI: 10.1134/s1070428012020030
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-chemical investigation of isocyanate reactions with linear methanol associates: V. Aryl isocyanate reactions with linear methanol associates

Abstract: The mechanism of addition of linear methanol associates (monomer, dimer, trimer) to aryl isocyanates at their C=N and С=О bonds was investigated applying the quantum-chemical method B3LYP/6-311++G(df,p). Notwithstanding the electronic character of substituents in the aromatic ring of the isocyanates all reactions proceed through concerted asymmetric late transition states. The addition to the C=N bond is considerably more preferable than to the С=О bond. In the transformations under consideration the intermol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…E a varies between 100.6 and 175.8 kJ/mol. The calculated energy values are comparable with previous DFT calculations for urea and urethane coupling reactions in the gas phase, confirming the validity of the current calculations of the reaction pathways. It is noted that the reported energies are electronic energies, not enthalpy ( H ) or Gibbs free energy ( G ).…”
Section: Resultssupporting
confidence: 88%
“…E a varies between 100.6 and 175.8 kJ/mol. The calculated energy values are comparable with previous DFT calculations for urea and urethane coupling reactions in the gas phase, confirming the validity of the current calculations of the reaction pathways. It is noted that the reported energies are electronic energies, not enthalpy ( H ) or Gibbs free energy ( G ).…”
Section: Resultssupporting
confidence: 88%
“…This Table 4. Thermodynamic parameters of activation of tautomerization of carbamate VI into azomethinenol VII in gas phase at 298 K: the non-catalytic and catalyzed by the methanol associates Ia-Ic ALCOHOL ASSOCIATES AS CATALYSTS OF TAUTOMERIC TRANSFORMATIONS has been shown for the alcohols reactions with alkyl- [23] and arylisocyanates [24] as well as isocyanic acid [25]; homo associates of phenol [26] and its mixed associates with methanol [27] are more reactive towards isocyanates than the monomeric alcohols; the same effect has been marked in the case of transesterification reactions [28]. The enhancement of reactivity upon association has been revealed for the hydrogen-bond complexes of amines: homo associates of amines [29] and their hetero associates with alcohols [30] are more reactive towards amides formation from esters as compared to the monomeric amines.…”
Section: Catalysis Of Carbamate-azomethinenol Tautomeric Transformatimentioning
confidence: 99%
“…The authors calculated and compared energy profiles of the different reaction paths and concluded that auto‐catalytic mechanisms are favored. In a series of studies, Samuilov et al [37,44−51] . investigated reactions of different isocyanates and alcohols based on B3LYP.…”
Section: Introductionmentioning
confidence: 99%
“…investigated reactions of different isocyanates and alcohols based on B3LYP. The authors compared enthalpies, entropies and free energies of activation for the reaction of the alcohol hydroxy group with the isocyanate C=N and C=O bonds, respectively [37,44−47] . Reactions were considered that proceed via transition states with 4‐rings (see Figures 1 and 2) as well as mechanisms with auto‐catalysis by methanol (Figure 2).…”
Section: Introductionmentioning
confidence: 99%